Is Mandarin essential to the construction of Chinese-ness in Singapore? - Wong, Kevin Zi Hao (2013)
This study consists of a discourse analysis and a questionnaire, both oriented towards an understanding of the value of Mandarin, as it underlies state construction of Chinese-ness, and as it is perceived by ordinary Chinese Singaporeans. Political discourse constructs Mandarin as essential to the construction of Chinese-ness in Singapore, insofar as it is the common language of all Chinese Singaporeans, and gives them access to their heritage in ancient Chinese civilisation. The questionnaire results show little evidence that Chinese Singaporeans share their leaders’ construction of Mandarin in relation to Chinese-ness. Chinese Singaporeans value Mandarin for mainly instrumental reasons, and this value is invested in an exonormative standard. Meanwhile, in local contexts, Chinese-ness is constructed not only through Mandarin, but Chinese dialects and English as well. The findings reveal a mismatch between official and unofficial constructions of Mandarin in Singapore, and point towards limitations in language planning in Singapore.